Olle Höök Lectureship 2019: The changing world of stroke rehabilitation - Katharina S. Sunnerhagen (Medical Journals Sweden, 2020)
The paper presents a summary of the Olle Höök lecture, which was presented at the Baltic North-Sea Forum in Oslo, Sweden, in October 2019. The paper aims to provide a worldwide picture of stroke, developments in this field, and the evolution of stroke rehabilitation. It sets out the background to, evidence for, and content of the comprehensive stroke unit. The paper also describes some rehabilitation techniques based on neurophysiology, the use of robotics, and the evidence level for interventions. Organization of the stroke care chain and different aspects of rehabilitation during its trajectory are described. However, the need for rehabilitation is often not met, due to restricted and unevenly distributed resources. With increasing knowledge of neurophysiology and evidence from meta-analyses, the content of stroke rehabilitation will continue to evolve.